2020
DOI: 10.1007/s00381-020-04717-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of children and adolescents with NF1 microdeletions

Abstract: Purpose An estimated 5–11% of patients with neurofibromatosis type 1 (NF1) harbour NF1 microdeletions encompassing the NF1 gene and its flanking regions. The purpose of this study was to evaluate the clinical phenotype in children and adolescents with NF1 microdeletions. Methods We retrospectively analysed 30 children and adolescents with NF1 microdeletions pertaining to externally visible neurofibromas. The internal tumour load was determined by volumetry of whole-body magnetic resonance imaging (MRI) in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 101 publications
(195 reference statements)
1
21
0
2
Order By: Relevance
“…Cutaneous neurofibromas show age-related penetrance and they usually appear in adulthood, therefore this may contribute to the difference in frequency observed by us and by others. Nevertheless, a high frequency (60%) of cutaneous neurofibromas was observed among children by Kehrer-Sawatzki in a recent study (Kehrer-Sawatzki et al, 2020). The high prevalence of subcutaneous neurofibromas in type-1 NF1 patients is important to consider, since they are associated with mortality in NF1 disease (Tucker et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cutaneous neurofibromas show age-related penetrance and they usually appear in adulthood, therefore this may contribute to the difference in frequency observed by us and by others. Nevertheless, a high frequency (60%) of cutaneous neurofibromas was observed among children by Kehrer-Sawatzki in a recent study (Kehrer-Sawatzki et al, 2020). The high prevalence of subcutaneous neurofibromas in type-1 NF1 patients is important to consider, since they are associated with mortality in NF1 disease (Tucker et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…However, it is important to emphasize that the majority of our patients (13 out of 17) were less than 15 years old at the time of the examination. There are only few studies ( Kehrer-Sawatzki et al, 2020 ) that demonstrated pediatric clinical data, the majority of phenotypic data published previously originated mainly from adult patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental delay observed in patient 310221 was much less severe than the global developmental delay frequently observed in children with type 1 or very large atypical NF1 microdeletions (reviewed in [5]). Severe global developmental delay in language and motor skills has been observed in 28 (93%) of 30 children with NF1 microdeletions [51]. These delays were already apparent at a young age (1-3 years) and persisted during later childhood.…”
Section: Discussionmentioning
confidence: 99%
“…These patients frequently exhibit more severe clinical manifestations of NF1 as well as features that are not frequently seen in patients with intragenic NF1 mutations. The type 1 NF1 deletion-associated phenotype includes facial dysmorphic features, severe global developmental delay, significantly lower full-scale IQ scores, higher neurofibroma burden and an increased risk of malignant peripheral nerve sheath tumours (MPNSTs) as compared to patients with intragenic NF1 mutations [5,[51][52][53][54]. It has been postulated that some of the genes located within the type 1 NF1 microdeletion region and co-deleted with NF1 exert an influence on the clinical manifestation of the disease in NF1 deletion patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 Lower extremity alignment films, at age 13 years 10 months. The image demonstrates improvement in the leg length discrepancy to just over 2 cm syndrome is typically characterized by a more severe clinical presentation than that seen in the majority of NF1 patients, with more cutaneous, subcutaneous and externally visible plexiform neurofibromas than agematched patients with intragenic NF1 mutations, in addition to facial dysmorphic features, cognitive impairment, developmental delay, and an increased risk of malignant tumors [15][16][17]. This patient demonstrates developmental delay, is non-verbal but able to follow simple commands and has short stature, all of which can be found in NF1, but these features fit a wide variety of genetic disorders besides NF1 and acroscyphodysplasia.…”
Section: Discussionmentioning
confidence: 99%